2014
DOI: 10.1111/apa.12786
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in indigenous Sami schoolchildren in Sweden

Abstract: In some aspects of HRQOL, indigenous Sami schoolchildren with an explicit ethnic identity experienced less favourable functioning and well-being than Swedish children in general, which is worrisome. A high degree of ethnicity-related negative treatment may partly explain this lower HRQOL in Sami children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Sami men are feeling healthier than women. Regarding youth samples, there are different results between different studies [12][13][14][15][16]20]. Mortality and life expectancy were similar between Sami and non-Sami population, with only minor differences.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Sami men are feeling healthier than women. Regarding youth samples, there are different results between different studies [12][13][14][15][16]20]. Mortality and life expectancy were similar between Sami and non-Sami population, with only minor differences.…”
Section: Discussionmentioning
confidence: 84%
“…On the SF-36 questionnaire used to assess the health-related quality of life, both men and women scored higher on physical function than the reference population, but lower on the included general health scales [19]. Among Sami schoolchildren in Sweden, the health-related quality of life was lower than for Swedish schoolchildren in general [20].…”
Section: Countriesmentioning
confidence: 81%
“…Previous research has found that Sami (the indigenous people of Sweden) children experience lower HRQOL in some domains compared with Swedish children in general. 6 In relation to HRQOL as it pertains to weight, and the impact of ethnicity, it is acknowledged that information about the relationship between HRQOL and weight may not have transferability from one cultural context to another, given differing perceptions of body image cross-culturally. 7 8 …”
Section: Introductionmentioning
confidence: 99%
“…The article by Omma and Petersen in this issue of the Journal makes an important contribution to our knowledge of the social determinants of health for Sami youth in Sweden and also has implications for understanding other indigenous populations . The authors studied correlates of health‐related quality of life (HRQoL) among 121 Sami adolescents from 12 to 18 years of age in Sweden.…”
mentioning
confidence: 99%